Impact of ovalbumin allergy on oral and gut microbiome dynamics in 6-week-old BALB/c mice - Qiao, Chuanyue; Bian, Shuang; Huang, Hao; Xiao, Han; Ma, Lei; Han, Rui (Frontiers in Microbiology, 2024)
Background The gut microbiota is known to have a significant impact on the development of food allergy, and several recent studies have suggested that both oral microbiota, which first come into contact with allergenic foods, may have a profound influence on the development of food allergy. Methods In this study, we have established an ovalbumin-sensitive mice model by utilizing ovalbumin as a sensitizing agent. Subsequently, we performed a comprehensive analysis of the gut and oral microbiota in ovalbumin-sensitive mice and the control mice using full-length 16S rRNA sequencing analysis. Results Interestingly, both the gut and oral microbiota of ovalbumin-sensitized mice exhibited significant dysbiosis. The relative abundance of s__Lactobacillus_intestinalis in the gut microbiota of ovalbumin-sensitive mice exhibited a significant decrease, whereas the abundance of s__Agrobacterium_radiobacter and s__Acinetobacter_sp__CIP_56_2 displayed a significant increase. Furthermore, the relative abundance of s__unclassified_g__Staphylococcus, s__Streptococcus_hyointestinalis, and s__unclassified_g__Dechloromonas in the oral microbiota of ovalbumin-sensitive mice revealed a significant decrease. In contrast, the abundance of 63 other species, including s__Proteiniclasticum_ruminis, s__Guggenheimella_bovis, and s__Romboutsia_timonensis, demonstrated a significant increase. The random forest classifier achieved the best accuracy in predicting the outcome of food allergy using three gut and three oral biomarkers, with accuracies of 94.12 and 100%, respectively. Based on the predictions of the PICRUSt2 analysis, the only consistent finding observed across multiple samples from both the groups of mice was a significant up-regulation of the nucleotide-binding oligomerization domain (NOD)-like receptor signaling pathway in the ovalbumin-sensitized mice. Conclusion Our study demonstrates that ovalbumin-sensitized mice experience substantial alterations in both gut and oral microbial composition and structure, and specific strains identified in this study may serve as potential biomarkers for food allergy screening. Moreover, our findings highlight that the oral environment, under the same experimental conditions, exhibited greater precision in detecting a larger number of species. Additionally, it is worth noting that the NOD-like receptor signaling pathway plays a vital role in the pathogenesis of OVA (ovalbumin)-induced allergy. These findings will generate novel concepts and strategies in the realm of food allergy prevention and treatment.